2021
DOI: 10.1088/1402-4896/ac418f
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of axisymmetric Sezawa waves in elastic solids

Abstract: The wave propagation in elastic solids covered by a thin layer has received significant attention due to the existence of Sezawa waves in many applications such as medical imaging. With a Helmholtz decomposition in cylindrical coordinates and subsequent solutions with Bessel functions, it is found that the velocity of such Sezawa waves is the same as the one in Cartesian coordinates, but the displacement will be decaying along the radius with eventual conversion to plane waves. The decaying with radius exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…This is different from the Cartesian solutions with constant amplitudes. The reason for such a feature is that the displacement solutions, as given in (33) and earlier studies [11][12][13], are in the Bessel functions with the cylindrical formulation, which decay with the radius and can eventually be approximated as trigonometric functions with a large radius, while the Cartesian formulation with trigonometric solutions has the constant amplitudes. Of course, the dispersion relations with the two formulations are exactly the same.…”
Section: Generalized Stoneley Wave In a Three-layer Structurementioning
confidence: 98%
See 1 more Smart Citation
“…This is different from the Cartesian solutions with constant amplitudes. The reason for such a feature is that the displacement solutions, as given in (33) and earlier studies [11][12][13], are in the Bessel functions with the cylindrical formulation, which decay with the radius and can eventually be approximated as trigonometric functions with a large radius, while the Cartesian formulation with trigonometric solutions has the constant amplitudes. Of course, the dispersion relations with the two formulations are exactly the same.…”
Section: Generalized Stoneley Wave In a Three-layer Structurementioning
confidence: 98%
“…For a semi-infinite space, either a Cartesian or cylindrical coordinate system is appropriate for formulating and solving problems concerning wave propagation for the wave velocity and displacements required in applications. Nevertheless, recent studies by our group have shown that the properties and features of waves are dependent on the chosen coordinate system and also show significant differences in the vicinity of the origin [11][12][13]. As such, the results obtained from different coordinate systems may vary, particularly if the configuration of materials and structures is uncertain or the concern is placed in the wave features near the origin of the coordinate system.…”
Section: Introductionmentioning
confidence: 99%
“…In elasticity, a surface wave on a free surface of a solid elastic body is usually called a Rayleigh wave. Rayleigh waves can be clearly distinguished from other types of wave, thus, their basic propagation properties have been studied in many areas, such as seismology and ultrasound [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Wave propagation in solids is an important topic for engineers and scientists in the related fields [1,2]. Particularly, dynamic response of structures under transient moving load has long been an interesting subject in the field of civil, transportation, geological and seismological engineering [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%